KEPENTINGAN AUSTRALIA DALAM BANTUAN LUAR NEGERI UNTUK PENGUNGSI ROHINGYA DI BANGLADESH - Achmad Raynaldi; Mega Agustina Kesumaning Pertiwi; Muhammad Indrawan Jatmika (Journal Publicuho, 2025)
This study aims to analyse the motives behind Australia's provision of foreign aid to Rohingya refugees in Bangladesh in the period 2017-2024. Using a qualitative approach with explanatory analysis, this study found that Australia's aid was not only based on humanitarian considerations, but also on political, security, environmental and moral interests. Politically, aid is used as a diplomatic instrument to strengthen Australia's influence in the Indo-Pacific region and maintain regional stability. Security-wise, aid is directed at preventing irregular migration. Meanwhile, environmental motives are reflected in the commitment to strengthening climate resilience, and moral motives appear through programs that support the dignity and quality of life of refugees. The findings in this study indicate that foreign aid policy cannot be separated from national interests, and that handling humanitarian crises requires the integration of moral values and strategic considerations.